Communication and Political Marketing as Elements of Electoral Training. The On and the Off During the First Electoral Round for the Ecuadorian Presidential Election in 2017 - Estrella-Osorio, Arturo Virgilio (2019)
This paper analyzes the characteristics of communication and marketing of politicians as elements of voter education, in the context of an electoral campaign on a presidential scale. In this case, the elective process of February 2017 in Ecuador. The research is designed to determine the conditions and methods that Ecuadorian political groups work in the fields of communication and marketing, and thus know the impact on the critical formation of voters. At the same time, it aims to identify the parameters and persuasive influences in which lines of thought are carried out in the electoral campaigns. For the analysis, the Facebook platform is used as a campaign space on the site (in which the predominant features and contents are presented and affected). These spaces correspond to the candidates who obtained the first places in the first electoral round: Lenin Moreno, Guillermo Lasso, Cynthia Viteri and Paco Moncayo. Then the data collection by interviews with a political analyst and two strategies of the currents of thought.